GRAMMATICAL FEATURES OF BLESSINGS AND WISHES IN ENGLISH AND UZBEK (Ustozlar uchun, 2025)
This study offers a comprehensive grammatical investigation of blessings and wishes in English and Uzbek, focusing on verb forms, mood, modality, and sentence structures. Blessings and wishes, as linguistic expressions of goodwill and desires, exhibit language-specific grammatical encoding shaped by typological and cultural features. English mostly uses modal auxiliaries, the subjunctive mood, and lexical verbs such as wish to construct blessings and wishes. In contrast, Uzbek employs rich agglutinative morphology with mood-marking suffixes including -sin, and special syntactic constructions.